Developing Machine Learning Algorithms on Routinely Collected Administrative Health Data - Lessons from Ontario, Canada. - Vinyas Harish; Mathieu Ravaut; Seung Eun Yi; Jahir Gutierrez; Hamed Sadeghi; Kin Kwan Leung; Tristan Watson; Kathy Kornas; Tomi Poutanen; Maksims Volkovs; Laura Rosella (International Journal of Population Data Science, 2022)
There has been considerable growth in the development of machine learning models for clinical applications; however, less attention has been paid to applications at the health systems level. Here, we survey recent models developed using provincial administrative health data holdings in Ontario, Canada to synthesize key learnings across use cases.